Assessment of real‐time and quantitative changes in renal hemodynamics in healthy overweight males: Contrast‐enhanced ultrasonography vs para‐aminohippuric acid clearance. (26th August 2019) - Muskiet, Marcel H. A.; Emanuel, Anna L.; Smits, Mark M.; Tonneijck, Lennart; Meijer, Rick I.; Joles, Jaap A.; Serné, Erik H.; van Raalte, Daniël H.
Abstract: Objective: To determine the ability of renal contrast‐enhanced ultrasonography (CEUS) to detect acute drug‐induced changes in renal perfusion (using the glucagon‐like peptide (GLP)‐1 receptor agonist exenatide and nitric oxide [NO]‐synthase inhibitor L‐N G ‐monomethyl arginine [l ‐NMMA]), and assess its correlation with gold standard‐measured effective renal plasma flow in humans. Methods: In this prespecified exploratory analysis of a placebo‐controlled cross‐over study, renal hemodynamics was assessed in 10 healthy overweight males (aged 20‐27 years; BMI 26‐31 kg/m 2 ) over two separate testing days; during placebo (isotonic saline) and subsequent exenatide infusion (Day‐A), and during l ‐NMMA, and subsequent exenatide plus l ‐NMMA infusion (Day‐B). Renal cortical microvascular blood flow was estimated following microbubble infusion and CEUS destruction‐refilling‐sequences. Renal cortical microvascular blood flow was compared with simultaneously measured effective renal plasma flow in humans, derived from para‐aminohippuric acid‐clearance methodology. Results: On Day‐A, effective renal plasma flow increased by 68 [26‐197] mL/min/1.73 m 2 during exenatide vs placebo infusion (+17%; P = .015). In parallel, exenatide increased renal cortical microvascular blood flow, from 2.42 × 10 −4 [6.54 × 10 −5 ‐4.66 × 10 −4 ] AU to 4.65 × 10 −4 [2.96 × 10 −4 ‐7.74 × 10 −4 ] AU (+92%; P = .027). On Day‐B, effective renal plasma flow and renal cortical microvascular blood flow were reduced by l ‐NMMA, with no significant effect of concomitant exenatide on renal hemodynamic‐indices assessed by either technique. Effective renal plasma flow correlated with renal cortical microvascular blood flow on Day‐A ( r = .533; P = .027); no correlation was found on Day‐B. Conclusions: Contrast‐enhanced ultrasonography can detect acute drug‐induced changes human renal hemodynamics. CEUS‐assessed renal cortical microvascular blood flow moderately associates with effective renal plasma flow, particularly when perfusion is in normal‐to‐high range. Renal CEUS cannot replace effective renal plasma flow measurements, but may be a complementary tool to characterize regional kidney perfusion.